Caffey Disease: A Diagnostic Dilemma - Regmi, Shanti; Adhikari, Sudhir; Sitaula, Deekshanta; Regmi, Ananda Prasad; Neupane, Gaurav; Parajuli, Biraj; Poudel, Sumita (Journal of Nepal Paediatric Society, 2021)
Caffey disease is a rare, self limiting condition which usually presents in early infancy. The clinical features include fever, irritability, inflammatory swelling of soft tissue due to acute inflammation of the periosteum and subperiosteal new bone formation. Possible differential diagnoses are osteomyelitis, hypervitaminosis A, scurvy, bone tumours, prolonged use of Prostaglandin E1 (PGE1) and child abuse. Although self-limiting, it can cause diagnostic dilemma leading to delayed diagnosis and unnecessary investigations. Here, we report a case of two month old male infant presenting with painful left scapular mass.